Peak stress studies of hot compressed TiHy 600 alloy. (2017) - Basanth Kumar, K.; Saxena, Kuldeep K.; Dey, Suhash R.; Pancholi, Vivek; Bhattacharjee, Amit
Abstract: TiHy 600 is a near alpha titanium alloy similar to IMI 834 Ti alloy, widely used for gas turbine engine applications such as disc and blades for high pressure compressors. Flow behavior of TiHy 600 alloy is investigated by conducting hot compression tests at temperatures ranging from 900°C to 1050°C with in the strain rate range of (0.001/s) respectively up to 50% deformation. Constitute modeling of work hardening is established, using Cingara equation to verify the stress up to peak stress. It was found that experimental true stress-true strain curves are in good agreement with Cingara equation curves for all temperatures at strain rate of (0.001/s)up to their peak stress values. The average activation energy (Q) is calculated from the peak stress of the flow curves using the hyperbolic-sine law equation (Arrhenius equation) i.e. 851.506KJ/mol. The microstructures of 50% deformed samples are correlated with the post-peak stress flow curve, performed mainly to compare the various softening processes (DRV or DRX).